Research on performance of refrigeration centrifugal compressor with gas bearings for water chillers. (November 2022) - Yi, Kexin; Zhao, Yuanyang; Yu, Guoxin; Yang, Qichao; Liu, Guangbin; Li, Liansheng
Abstract: As an important device for water chillers, the centrifugal refrigeration compressor with gas bearings has new features compared with traditional oil and magnetic bearings. It is an important development direction for water chillers and needs to be studied. To research the performance of compressors for water chillers, the R134a centrifugal refrigeration compressor with gas bearings is researched by the computation fluid dynamics (CFD) method. The prototype of the two-stage centrifugal compressor was tested in the water chiller. The test bench of the centrifugal chiller has two kinds of gas supply systems for gas bearings. The axial force of impellers is simulated under different working conditions by the CFD method. Compared with the two-stage impeller in the same direction arrangement, the opposite direction arrangement can reduce the total axial force of the rotor by up to 98.3%. The simulation performance of gas bearings and test results show that the gas bearings can bear the axial force caused by the gas force of two impellers. The results from the simulation and experiment are compared with the average error of 4.3% when the rotating speed is 21000 r ⋅ min − 1 . Highlights: R134a centrifugal refrigeration compressors with gas bearings are researched. Two kinds of gas supply systems for gas bearings are proposed. The axial force of impellers and the load capacity of bearings are simulated. The gas bearings can bear the axial force caused by the gas force of two impellers. The opposite direction arrangement of impellers can reduce the total axial force by up to 98.3%.